Inovação biotecnológica para biorremediação de manguezais contaminados com derivados do petróleo - Alves, Bella Giselly Torres (2023)
Mangroves are highly vulnerable to oil spills. The decontamination of these environments by hydrocarbon-degrading microorganisms stands out as a sustainable bioremediation alternative. This study aimed to validate a consortium of two hydrocarbonoclastic actinobacteria, previously isolated from mangrove, identified as Gordonia sp. HEX 5 and Micrococcus sp. HEX 6 for application in bioremediation of hydrocarbon-contaminated soils. First, the presence of the alkB gene in the consortium bacteria was evaluated through PCR using specific primers. Their ability to use hexadecane as a carbon source in mineral medium cultivation was also evaluated. Subsequently, the consortium was immobilized in chitosan spheres and tested in microcosms of mangrove sediment contaminated with 1% hexadecane. Other bioremediation strategies were also carried out in microcosms for comparison and control. The experiment lasted for 60 days, and the tested microcosms received the contaminant at the beginning and after 30 days. Treatments and controls were monitored by measuring dehydrogenase activity (DHA) and changes in bacterial community through sequencing of the 16S ribosomal RNA gene. The results showed that although both bacterial strains used hexadecane as the only carbon source, the alkB gene was detected in only one of them. In the microcosms, evidence of biodegradation was detected on the 3rd day after contamination in the groups inoculated with the consortium, with maximum degradation on the 12th day. After the 2nd contamination, in 30 days, the response was faster and more lasting. Chitosan stimulated the biodegradation, whereas the addition of biosurfactants did not show influence. Significant changes in the bacteriome were observed with the temporal succession of groups involved in biodegradation. At the peak of biodegradation, the bacteriome was enriched with the phyla Proteobacteria, Firmicutes, and Bacteroidetes, with higher abundance of Fusibacter, Flavobacterium, Vibrio, and Fontimonas. The tested technology proved to be capable of stimulating the autochthonous microbiota and accelerating alkane degradation in microcosms.This study gave rise to a product called BioClineX, with a patent submitted to INPI. It also gave rise to the startup Biotech4life Solutions, enabling the transformation of knowledge derived from science into marketable products that have a positive impact on the market and society.